BZMT transparent ceramic, preparation method thereof and optical element
By regulating the solid content and Zeta potential of the ceramic slurry, the static settlement process is used to form in ordinary molds and directly sintered in one step, solving the problems of complex and insufficient density of the existing BZMT transparent ceramic preparation process, achieving high transmittance and low scattering point BZMT transparent ceramic.
Patent Information
- Application Number
- CN202411187519.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-13
AI Technical Summary
The existing BZMT transparent ceramics have complex preparation processes and high equipment costs. The ceramic density is not high enough due to the addition of organic binders, which has light scattering problems, which affects the optical properties of transparent ceramics.
By regulating the solid content, Zeta potential and viscosity of the ceramic slurry, the BZMT transparent ceramic is formed in ordinary molds by using a static settlement process. There is no need to add organic binder or use dry-pressure-cold isostatic pressing process, and BZMT transparent ceramics are directly sintered in one step to make .
The preparation process is simplified, the production cost is reduced, the density and transmittance of the ceramic is increased, the haze value is reduced, and the BZMT transparent ceramic with high transmittance and low scattering points is achieved.
Smart Images

Figure CN119118663A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of transparent ceramics, and in particular to a BZMT transparent ceramic and a preparation method thereof, and an optical element. Background Art
[0002] The theoretical transmittance of Ba(Zr,Mg,Ta)O3(BZMT) transparent ceramics is 77.1%. After double-sided coating, the transmittance can reach more than 99%. It has strong corrosion resistance, high refractive index, and is easy to process. It can directly apply glass lens processing templates and production processes. It has the advantage of mass production and is therefore widely used in lens group thinning, mobile phone camera thinning, and security monitoring fields.
[0003] In the prior art, the preparation method of BZMT transparent ceramics mainly includes the following steps: (1) preparing BZMT ceramic powder by solid phase method; (2) mixing ceramic powder, organic binder and dispersant to prepare ceramic slurry; (3) drying and grinding the ceramic slurry, placing it in a dry press for pre-pressing, and then placing it in a cold isostatic press for cold isostatic pressing to obtain a green blank; (4) debinding the green blank; (5) sintering the debinded green blank to obtain BZMT transparent ceramics. The entire preparation process is complicated and the equipment cost is high. In addition, since an organic binder needs to be added to coagulate the slurry, the density of the ceramic is not high enough, and there are many light scattering sources, such as pores, grain boundaries, impurities and other birefringence effects, which affect the optical properties of the transparent ceramics. Summary of the invention
[0004] To solve the above problems, the purpose of the embodiments of the present application includes providing a BZMT transparent ceramic and a preparation method thereof, which can simplify the preparation process, reduce production costs, and improve ceramic scattering without affecting the transparency.
[0005] In a first aspect, the present application provides a method for preparing a BZMT transparent ceramic, comprising the following steps:
[0006] Prepare ceramic slurry: Ba(Zr x Mg y Ta z )O3 ceramic powder is mixed with a dispersant and water to obtain a ceramic slurry; wherein x+y+z=1, x>0, y>0, z>0; the solid content of the ceramic slurry is 70% to 90%, and the Zeta potential is (-25 to -31) mV or (25 to 31) mV; when the shear rate is 10 (1 / s), the viscosity of the ceramic slurry is 300 to 550 mPa.s;
[0007] Forming green embryo: inject the ceramic slurry into the mold, let it settle, and obtain the green embryo;
[0008] Ceramic sintering: The green body is sintered at a certain temperature to obtain BZMT transparent ceramics.
[0009] In the above technical scheme, by regulating the solid content, Zeta potential and viscosity of the ceramic slurry, there is no need to add an organic binder, and there is no need to use complex processes such as dry pressing-cold isostatic pressing. The green blank can be obtained by static sedimentation in an ordinary mold. There is no need for binder removal before sintering, and BZMT transparent ceramics can be obtained by one-step sintering. The entire preparation method is simple and easy to control, and there are no special requirements for ceramic powders and molds. The equipment is simple and the production cost is low. It can achieve rapid batch large-scale production, and the molding cycle is short. In addition, compared with the BZMT transparent ceramics prepared by conventional methods, the BZMT transparent ceramics obtained by the above preparation method have no significant reduction in transmittance and have a relatively lower haze value, that is, the BZMT transparent ceramics have high transmittance and low scattering points.
[0010] In some embodiments of the present application, the dispersant includes isobutylene-maleic anhydride copolymer and ammonium citrate, and the amount of isobutylene-maleic anhydride copolymer is the amount of Ba(Zr x Mg y Ta z )O3 ceramic powder, the amount of ammonium citrate is 0.01wt% to 0.5wt% of the mass of the Ba(Zr x Mg y Ta z )0.1wt% to 0.4wt% of the mass of O3 ceramic powder.
[0011] In the above technical solution, by selecting a specific dispersant and adjusting the amount of the dispersant added, the viscosity and Zeta potential of the ceramic slurry can be effectively controlled, thereby controlling the dispersibility and stability of the slurry. The slurry can be perfectly dried and formed during the injection molding process, so no binder is required.
[0012] In some embodiments of the present application, the Zeta potential of the ceramic slurry is -29 mV to -31 mV.
[0013] In the above technical solution, the Zeta potential of the ceramic slurry is around plus or minus 30 mV, which can maintain the stability of the ceramic slurry system.
[0014] In some embodiments of the present application, the mixing method is ball milling for 8 to 32 hours.
[0015] In the above technical solution, the ball milling time may affect the dispersion uniformity of the ceramic slurry to a certain extent.
[0016] In some embodiments of the present application, the static sedimentation includes: allowing the ceramic slurry to naturally settle in the mold for 0.5-3 hours.
[0017] Since the solid content of the ceramic slurry is relatively high, it will naturally settle for a period of time, and the water will evaporate and dry, then the green body can be demoulded to obtain.
[0018] In some embodiments of the present application, the sintering conditions include: sintering in an oxygen atmosphere at a temperature of 1150 to 1680° C. for 5 to 10 hours.
[0019] In the above technical solution, since the green body has a high density and contains only a small amount of organic matter, transparent ceramics can be obtained by sintering in a short time at a relatively low temperature in one step.
[0020] In some embodiments of the present application, Ba(Zr x Mg y Ta z ) The preparation method of O3 ceramic powder comprises:
[0021] Barium carbonate, magnesium oxide, zirconium oxide and tantalum oxide are mixed in a certain proportion, ball milled, dried and calcined by a solid phase method to obtain Ba(Zr x Mg y Ta z )O3 ceramic powder.
[0022] In a second aspect, an embodiment of the present application provides a BZMT transparent ceramic prepared by the above-mentioned preparation method.
[0023] In a third aspect, an embodiment of the present application further provides an optical element, comprising the above-mentioned BZMT transparent ceramic.
[0024] BZMT transparent ceramics have high transmittance and low scattering point, a haze value of less than 1.4%, a transmittance of more than 73% at a wavelength of 650nm, and a simple preparation method and can be mass-produced, so they can be effectively used to make optical components. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a process flow chart of the preparation method of BZMT transparent ceramics provided in an embodiment of the present application.
[0027] Figure 2 A schematic diagram of an optical element provided in an embodiment of the present application.
[0028] Figure 3 This is a Zeta potential distribution curve of the ceramic slurry prepared in Example 1 of the present application.
[0029] Figure 4 This is a viscosity curve of the ceramic slurry prepared in Example 1 of the present application at different shear rates.
[0030] Figure 5 This is a physical diagram of the molding process in Example 1 of the present application; wherein, Figure 5 (A) is a real picture of the ceramic slurry being placed in the mold; Figure 5 (B) is a real picture of the ceramic slurry after natural sedimentation in the mold; Figure 5 (C) is a real picture of the blank formed by demoulding from the mold.
[0031] Figure 6 This is a Zeta potential distribution curve of the ceramic slurry prepared in Example 2 of the present application.
[0032] Figure 7 This is a viscosity curve of the ceramic slurry prepared in Example 2 of the present application at different shear rates.
[0033] Figure 8 This is a Zeta potential distribution curve of the ceramic slurry prepared in Example 3 of the present application.
[0034] Fig. 9 This is a viscosity curve of the ceramic slurry prepared in Example 3 of the present application at different shear rates.
[0035] Fig.10 This is a Zeta potential distribution curve of the ceramic slurry prepared in Comparative Example 2 of the present application.
[0036] Fig.11 This is a viscosity curve of the ceramic slurry prepared in Comparative Example 2 of the present application at different shear rates.
[0037] Fig.12 This is an optical image of the blank prepared in step (2) of comparative example 2 of the present application.
[0038] Fig.13 This is a Zeta potential distribution curve of the ceramic slurry prepared in Comparative Example 3 of the present application.
[0039] Fig.14 This is a viscosity curve of the ceramic slurry prepared in Comparative Example 3 of the present application at different shear rates.
[0040] Fig.15 This is an optical image of the blank prepared in step (2) of comparative example 3 of the present application.
[0041] Fig.16 This is the XRD pattern of the BZMT transparent ceramic prepared in Example 1 of the present application.
[0042] Fig.17This is a transmittance curve of the BZMT transparent ceramic prepared in Example 1 of the present application.
[0043] Fig.18 This is a transmittance curve of the BZMT transparent ceramic prepared in Example 2 of the present application.
[0044] Fig.19 This is a transmittance curve of the BZMT transparent ceramic prepared in Example 3 of the present application.
[0045] Fig. 20 This is the XRD diagram of the BZMT transparent ceramic prepared in Comparative Example 1 of the present application.
[0046] Fig.21 This is a transmittance curve of the BZMT transparent ceramic prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0047] Figure 1 This is a process flow chart of the preparation method of BZMT transparent ceramics provided in the embodiment of the present application. Figure 1 The preparation method of BZMT transparent ceramic provided in the present application comprises the following steps:
[0048] S110, prepare ceramic slurry: Ba(Zr x Mg y Ta z )O3 ceramic powder is mixed with a dispersant and water to obtain a ceramic slurry; wherein x+y+z=1, x>0, y>0, z>0; the solid content of the ceramic slurry is 70% to 90%, and the Zeta potential is (-25 to -31) mV or (25 to 31) mV; when the shear rate is 10 (1 / s), the viscosity of the ceramic slurry is 300 to 550 mPa.s.
[0049] The dispersant includes isobutylene-maleic anhydride copolymer and ammonium citrate, and the amount of isobutylene-maleic anhydride copolymer is Ba(Zr x Mg y Ta z )O3 ceramic powder, the amount of ammonium citrate is 0.01wt% to 0.5wt% of the mass of Ba(Zr x Mg y Ta z )0.1wt% to 0.4wt% of the mass of O3 ceramic powder.
[0050] Isobutylene-maleic anhydride copolymer can be used to regulate the viscosity of ceramic slurry, and ammonium citrate can ionize ions to produce electrostatic repulsion and adjust the Zeta potential of ceramic slurry. The two work together to achieve low viscosity, high solid phase slurry through the composite stabilization effect of electrostatic repulsion and steric hindrance.
[0051] Among them, Zeta potential can be used as an indicator of the stability of the colloidal system. Generally speaking, when the Zeta potential is around plus or minus 30 mV, the dispersion system can be maintained stable. In the embodiment of the present application, the preferred Zeta potential is -29 mV to -31 mV.
[0052] The mixing method is ball milling, and the time can be 8 to 32 hours.
[0053] By controlling the amount of water added, the solid content of the ceramic slurry can be controlled to 70% to 90%. Combined with controlling the amount of dispersant and the ball milling time, the potential and viscosity of the ceramic slurry can be effectively regulated, thereby controlling the dispersibility and stability of the ceramic slurry.
[0054] In the present application, Ba(Zr x Mg y Ta z The preparation method of Ba(Zr)O3 ceramic powder may include the following steps: mixing barium carbonate, magnesium oxide, zirconium oxide and tantalum oxide in a certain proportion, ball milling, drying and calcining the mixed raw materials by a solid phase method to obtain Ba(Zr)O3 ceramic powder. x Mg y Ta z )O3 ceramic powder.
[0055] Preferably, Ba(Zr x Mg y Ta z )O3 ceramic powder is Ba(Zr 0.16 Mg 0.28 Ta 0.56 )O3 ceramic powder.
[0056] Optionally, an appropriate amount of ethanol and a dispersant may be added during the ball milling process, and the ball milling may be performed for 8 to 32 hours. The amount of ethanol added may be 0.8 to 1.2 times the mass of the mixed raw materials, and the amount of the dispersant added may be 0.1 wt% to 0.5 wt% of the mass of the mixed raw materials. As an example, the dispersant may be oleic acid or glycerol.
[0057] The drying method may include: transferring the ball-milled slurry into a glass dish and drying it in an oven at 50°C.
[0058] The calcination conditions may include: grinding the dried powder and calcining it in a box furnace at 1200-1400° C. for 5-10 hours.
[0059] S120, forming a green body: injecting the ceramic slurry into a mold, allowing it to settle, and obtaining a green body.
[0060] The static settling includes: allowing the ceramic slurry to statically settle in the mold for 0.5 to 3 hours.
[0061] Due to the characteristics of BZMT ceramic powder itself, it has a heavy density and good water-locking performance. During the vacuum grouting process into the mold, it is difficult to filter out the liquid. In the prior art, an organic binder is also added to the ceramic slurry to make it creamy and more viscous. Therefore, the solid content is lowered to adapt to vacuum grouting, resulting in the green body having insufficient density and defects. In the preparation method of the present application, there is no need to add an organic binder, the solid content is controlled to be 70% to 90%, and the slurry is controlled to have a suitable Zeta potential and viscosity, so that the ceramic slurry has good dispersibility and stability, and meets the requirements of low viscosity and high solid content. The green body can be obtained by natural sedimentation and drying in an ordinary mold.
[0062] S130, ceramic sintering: sintering the green body at a certain temperature to obtain BZMT transparent ceramics.
[0063] The sintering conditions include: sintering in an oxygen atmosphere at a temperature of 1150-1680° C. for 5-10 hours. After sintering, double-sided grinding is performed to obtain BZMT transparent ceramics with high transmittance.
[0064] In the above preparation method, by controlling the solid content, viscosity and potential of the ceramic slurry, the blank can be directly left to settle to obtain the blank, and the transparent ceramic with high transmittance can be obtained by one-step sintering. In addition, the preparation method has no special requirements for the ceramic powder and the mold, and can be mass-produced in batches quickly and in a short molding cycle. The blank has high strength and can be processed by CNC. It has low organic content, does not require debinding, and does not require the use of complex processes such as dry pressing-cold isostatic pressing. The blank and sintered body have good uniformity of performance, the process is easy to control, the process and operation are relatively simple, and the equipment is simple and low-cost, which is conducive to rapid industrial production.
[0065] It can be understood that the embodiments of the present application only list the use of this method to prepare BZMT transparent ceramics. In fact, this method can also be used to prepare other types of transparent ceramics, such as Ba(Zr,Mg,Nb)O3(BZMN) transparent ceramics, magnesium aluminum spinel transparent ceramics, lanthanum gadolinium zirconate transparent ceramics, etc.
[0066] The present application also provides a BZMT transparent ceramic prepared by the above preparation method.
[0067] In addition, an embodiment of the present application also provides an optical element, including the above-mentioned BZMT transparent ceramic.
[0068] The haze value of this BZMT transparent ceramic is less than 1.4%, and the transmittance at a wavelength of 650nm is greater than 73%. It has high transmittance and low scattering point, and can be effectively used as an optical component in optical elements, such as lenses, prisms, etc. Please refer to Figure 2The lens made of the BZMT transparent ceramic can be a double convex lens 1, a double concave lens 2, a pure transmission optical element 3 and a spherical lens 4.
[0069] Among them, the optical element can specifically be a camera lens group, a mobile phone camera, a surveillance camera, etc.
[0070] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0071] Example 1
[0072] This embodiment provides a BZMT transparent ceramic, and the preparation method thereof includes:
[0073] (1) Preparation of ceramic powder: Weigh barium carbonate (BaCO3), zirconium oxide (ZrO2), magnesium oxide (MgO) and tantalum oxide (Ta2O5) in a molar ratio of 1:0.16:0.28:0.28, add ethanol in a mass ratio of 1:1 to the mixed raw materials and a dispersant accounting for 0.2wt% of the mixed raw materials, place in a ball mill, and ball mill for 24h. Transfer the ball-milled slurry to a glass dish and dry it in an oven. After grinding the dried powder, calcine it in a box furnace at 1300℃ for 10h to obtain Ba(Zr 0.16 Mg 0.28 Ta 0.56 )O3 ceramic powder.
[0074] (2) Molding embryo: Ba(Zr 0.16 Mg 0.28 Ta 0.56 )O3 ceramic powder was mixed with 0.1wt% isobutylene-maleic anhydride copolymer (ISOBAM) and 0.25wt% ammonium citrate, and water was used as solvent, and the mixture was ball-milled for 24h to obtain a ceramic slurry. The solid content of the ceramic slurry was 80%, and the Zeta potential was -29.5mV (Zeta potential distribution curve is shown in Figure 3 ), when the shear rate is 10 (1 / s), the viscosity is 511mPa.s (see the viscosity curve Figure 4 ).like Figure 5 As shown, the ceramic slurry is brought into a plastic mold, allowed to settle for 1 hour to dry, and demolded to obtain a complete square green blank.
[0075] (3) Ceramic sintering: The green body is placed in a sintering chamber, industrial oxygen is introduced, and sintered at 1600°C for 8 h to obtain BZMT transparent ceramics.
[0076] Example 2
[0077] This embodiment provides a BZMT transparent ceramic, and its preparation method is substantially the same as that of embodiment 1, except that:
[0078] (2) Molding embryo: Ba(Zr 0.16 Mg 0.28 Ta 0.56 )O3 ceramic powder was mixed with 0.5wt% isobutylene maleic anhydride copolymer (ISOBAM) and 0.3wt% ammonium citrate by secondary ball milling with water as solvent to obtain ceramic slurry. The solid content of the ceramic slurry was 70% and the Zeta potential was -30.8mV (Zeta potential distribution curve see Figure 6 ), when the shear rate is 10 (1 / s), the viscosity is 477mPa.s (see the viscosity curve Figure 7 ).
[0079] Example 3
[0080] This embodiment provides a BZMT transparent ceramic, and its preparation method is substantially the same as that of embodiment 1, except that:
[0081] (2) Molding embryo: Ba(Zr 0.16 Mg 0.28 Ta 0.56 )O3 ceramic powder was mixed with 0.4wt% isobutylene maleic anhydride copolymer (ISOBAM) and 0.3wt% ammonium citrate by secondary ball milling with water as solvent to obtain ceramic slurry. The solid content of the ceramic slurry was 70% and the Zeta potential was -30.1mV (Zeta potential distribution curve see Figure 8 ), when the shear rate is 10 (1 / s), the viscosity is 355mPa.s (see the viscosity curve Fig. 9 ).
[0082] Comparative Example 1
[0083] This comparative example provides a BZMT transparent ceramic, and the preparation method thereof comprises:
[0084] (1) Preparation of ceramic powder: Weigh barium carbonate (BaCO3), zirconium oxide (ZrO2), magnesium oxide (MgO) and tantalum oxide (Ta2O5) in a molar ratio of 1:0.16:0.28:0.28, add ethanol in a ratio of 1:1 and 0.2wt% of dispersant oleic acid to the mixed raw materials, place in a ball mill, and ball mill for 24h. Transfer the milled slurry to a glass dish and dry it in an oven. After grinding the dried powder, calcine it in a box furnace at 1300℃ for 10h to obtain Ba(Zr 0.16 Mg 0.28 Ta 0.56 )O3 ceramic powder.
[0085] (2) Molding embryo: Ba(Zr 0.16 Mg 0.28 Ta 0.56 )O3 ceramic powder and 0.1wt% isobutylene maleic anhydride copolymer (ISOBAM), 0.25wt% ammonium citrate, 0.5wt% PVA binder, with water as solvent, adjusting the solid content to 80%, and secondary ball milling for 24h to obtain ceramic slurry. The ceramic slurry was dried and ground, placed in a stainless steel mold with a diameter of 15mm, dry pressed at 10Mpa, and then cold isostatically pressed at 180MPa for 180s to obtain a blank.
[0086] (f) Debinding: The green billet is treated at 700°C for 10 h for debinding.
[0087] (g) Sintering: The debinded green blank is placed in a sintering chamber, introduced with industrial oxygen, and sintered at 1600°C for 8 h to obtain BZMT transparent ceramics.
[0088] Comparative Example 2
[0089] This comparative example provides a BZMT transparent ceramic, the preparation method of which is substantially the same as that of Example 1, except that:
[0090] (2) Molding embryo: Ba(Zr 0.16 Mg 0.28 Ta 0.56 )O3 ceramic powder was mixed with 0.1wt% isobutylene maleic anhydride copolymer (ISOBAM) and 0.25wt% ammonium citrate by secondary ball milling with water as solvent to obtain ceramic slurry. The solid content of the ceramic slurry was 50% and the Zeta potential was -14.7mV (Zeta potential distribution curve see Fig.10 ), when the shear rate is 10 (1 / s), the viscosity is 3.6 mPa.s (see the viscosity curve Fig.11 The ceramic slurry was placed in a plastic mold and allowed to settle freely for 1 hour. The square green blank showed stratification (see Fig.12 ).
[0091] Comparative Example 3
[0092] This comparative example provides a BZMT transparent ceramic, the preparation method of which is substantially the same as that of Example 1, except that:
[0093] (2) Molding embryo: Ba(Zr 0.16 Mg 0.28 Ta 0.56)O3 ceramic powder and 0.1wt% isobutylene maleic anhydride copolymer (ISOBAM), 3wt% ammonium citrate, water as solvent, secondary ball milling for 24h to obtain ceramic slurry. The solid content of the ceramic slurry is 50%, and the Zeta potential is -24.5mV (Zeta potential distribution curve see Fig.13 ), when the shear rate is 10 (1 / s), the viscosity is 80mPa.s (see the viscosity curve Fig.14 Then the ceramic slurry was directly brought into the plastic mold and allowed to settle freely for 1 hour. The resulting green body showed cracking and delamination (see Fig.15 ).
[0094] Some of the preparation conditions of the above examples and comparative examples are shown in Table 1.
[0095] Table 1 Part of the preparation conditions in the examples and comparative examples
[0096]
[0097] Performance testing and result analysis
[0098] The viscosity and Zeta potential of the ceramic slurry prepared in Example 1 were tested, and the BZMT transparent ceramics prepared in the examples and comparative examples were tested for XRD, transmittance, and haze. The specific test methods are as follows:
[0099] (1) Viscosity: Anton Paar MCR92 equipment was used. For solutions with a viscosity below 10 Pas, the cylinder test method was used and the test was performed in accordance with ISO3219.
[0100] (2) Zeta potential: Anton Paar DLS500 equipment was used for electrophoretic light scattering (ELS) test of laser Doppler electrophoresis in accordance with the standard GB / T29022.
[0101] (3) XRD: German Bruker D8 Advance X-ray powder diffractometer was used, with a scanning range of 2θ = 10 to 90°, Cukα radiation And use standard JCPDS files for phase analysis.
[0102] (4) Transmittance / haze: Take a sample with a thickness of 1 mm and use a 3NH device to obtain the transmittance and haze values in the wavelength range of 360-780 nm according to the ASTM D1003 / 1044 test standard.
[0103] The test results of transmittance and haze value of each sample in Examples 1-3 and Comparative Example 1 are shown in Table 2:
[0104] Table 2 Transmittance and haze values of samples in Examples and Comparative Examples
[0105]
[0106] Depend on Fig.16 and Fig. 20 From the XRD curves, it can be seen that the products prepared in Example 1 and Comparative Example 1 are both BZMT transparent ceramics. Figure 17-19 , Fig.21 As shown in Table 1, the transmittance of the BZMT transparent ceramics prepared in Examples 1-3 is comparable to that of the BZMT transparent ceramics prepared by dry pressing-cold isostatic pressing in Comparative Example 1, with no significant decrease. When the wavelength is 1000nm, the transmittance can reach 76%, and the haze value is significantly better than that of Comparative Example 1, indicating that there are fewer scattering points in the transparent ceramics prepared in Examples 1-3. In addition, it can be seen from Comparative Examples 2 and 3 that when the solid content, Zeta potential and viscosity of the ceramic slurry do not meet the requirements, the green blanks prepared by the technical solution of the present application all show stratification, and it is impossible to prepare a BZMT transparent ceramic with a complete structure.
[0107] From the above, it can be seen that the present application improves the injection-gelling process, does not need to add organic binders, does not need to remove binders, only needs to control the solid content, viscosity and potential of the ceramic slurry, can simply and quickly form a green body, and does not need to use complex processes such as dry pressing-cold isostatic pressing. Compared with the products prepared by the conventional dry pressing-cold isostatic pressing method, the technical solution of the present application is more efficient in preparing green bodies, has more stable molding, has high green body strength, can be CNC processed, and the process is simple and easy to control. The transmittance of the prepared BZMT transparent ceramics did not decrease significantly, and the haze value was lower, that is, BZMT transparent ceramics with high transmittance and low scattering point were prepared.
[0108] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A method for preparing BZMT transparent ceramics, characterized in that: The steps include: Prepare ceramic slurry: Ba(Zr x Mg y Ta z )O3 ceramic powder is mixed with a dispersant and water to obtain a ceramic slurry; wherein x+y+z=1, x>0, y>0, z>0; the solid content of the ceramic slurry is 70% to 90%, and the Zeta potential is (-25 to -31) mV or (25 to 31) mV; when the shear rate is 10 (1 / s), the viscosity of the ceramic slurry is 300 to 550 mPa.s; Forming a green embryo: injecting the ceramic slurry into a mold, allowing it to settle, and obtaining a green embryo; Ceramic sintering: The green body is sintered at a certain temperature to obtain BZMT transparent ceramics.
2. The preparation method according to claim 1, characterized in that: The dispersant comprises isobutylene-maleic anhydride copolymer and ammonium citrate, and the amount of the isobutylene-maleic anhydride copolymer is x Mg y Ta z )O3 ceramic powder, the amount of ammonium citrate is 0.01wt% to 0.5wt% of the mass of the Ba(Zr x Mg y Ta z )0.1wt% to 0.4wt% of the mass of O3 ceramic powder.
3. The preparation method according to any one of claims 1 to 2, characterized in that The zeta potential of the ceramic slurry is -29mV to -31mV.
4. The preparation method according to claim 1, characterized in that: The mixing method is ball milling for 8 to 32 hours.
5. The preparation method according to claim 1, characterized in that: The static sedimentation comprises: allowing the ceramic slurry to naturally settle in the mold for 0.5 to 3 hours.
6. The preparation method according to claim 1, characterized in that: The sintering conditions include: sintering in an oxygen atmosphere at a temperature of 1150-1680° C. for 5-10 hours.
7. The preparation method according to claim 1, characterized in that: The Ba(Zr x Mg y Ta z ) The preparation method of O3 ceramic powder comprises: Barium carbonate, magnesium oxide, zirconium oxide and tantalum oxide are mixed in a certain proportion, ball-milled, dried and calcined by a solid phase method to obtain the Ba(Zr x Mg y Ta z )O3 ceramic powder.
8. A BZMT transparent ceramic, characterized in that: The method is prepared according to any one of claims 1 to 7.
9. The BZMT transparent ceramic according to claim 8, characterized in that: The haze value of the BZMT transparent ceramic is lower than 1.4%, and the transmittance at a wavelength of 650 nm is greater than 73%.
10. An optical element, characterized in that: The method comprises the BZMT transparent ceramic according to any one of claims 8 to 9.
Citation Information
Patent Citations
Novel transparent ceramic material and preparation method thereof
CN105669196A
Preparation method of large-size complex-shape high-transmittance lanthanum gadolinium zirconate transparent ceramics
CN113105233A
Translucent ceramic
JP2011001229A
